Uniqueness for Entropy Solutions to fully Nonlinear Equations - KOURAICHI, Chiraz; SIAI, Abdelmajid (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Let X be a metric space, the space of measurable funtions, be a domain whith boundary and a(x; ) be an operator of Leray-Lions type. If and are nondecreasing continuous function on R such that (0) = (0) = 0 and (f; g) L1 (X; ; ), then, there exists a unique entropy solution u in M(X; B; ) to the problem [a(.,Du)] + (u) = and a(.,Du)v+ (u) = g on .